Ecological Aspects of Phebotomine (Diptera, Psychodidae) in an Endemic Area of Tegumentary Leishmaniasis in the Northeastern Argentina, 1993-1998 - Salomón, Oscar Daniel (2002)
The first epidemic tegumentary leishmaniasis´ outbreak in the province of Misiones was recorded in 1998, in the locality of Puerto Esperanza. Phlebotominae collected in the region, previously or simultaneously to the outbreak (September 1993-December 1998) showed that the species Lutzomyia intermedia s. l. was prevalent (94%, n 6,150) at all the sites sampled with miniature light trap (10) and Shannon trap (3). L. pessoai, L. whitmani, L. migonei, L. shannoni, L. fischeri, L. misionensis, Brumptomyia avellari and B. guimaraesi were also captured. Sand fly distribution in time and space suggests that in the province of Misiones (1) the species already present before 1990 could give rise to the epidemic by the density/dispersion fluctuation of their local populations; (2) the abundance of L. intermedia s. l. was associated with environments with ecotones of primary-secondary vegetation, close to water bodies and with moderate human disturbance; (3) this species showed, towards the end of 1997, peaks of exceptional abundance, subsequent to rainfall peaks in 1996. This increase in abundance of potential vector sand fly populations close to houses with colonizable surroundings could have generated the 1998 epidemic outbreak.